Influencing factors of home hospice care needs of the older adults with chronic diseases at the end of life in China: a cross-sectional study - Wang, Lei; Li, Yaru; Zhao, Rui; Li, Jiangxu; Gong, Xiangru; Li, Hongyu; Chi, Yuan (Frontiers in Public Health, 2024)
Introduction Chronic diseases are becoming a serious threat to the physical and mental health of older people in China as their aging process picks up speed. Home hospice care addresses diverse needs and enhances the quality of life for older adult individuals nearing the end of life. To ensure the well-being of chronically ill older adults at the end of life, it is vital to explore and assess the multidimensional hospice needs of terminally ill older individuals in their homes. The aim of this study was to investigate the current situation of home hospice care needs of Chinese older adults with chronic diseases at the end of life, and to analyze the influencing factors (sociodemographic and disease-related factors). Methods In this cross-sectional study, 247 older adult people with chronic diseases at the end of life were selected from the communities of 4 community health service centers in Jinzhou City, Liaoning Province from June to October 2023 by random sampling method. A general information questionnaire and the home hospice care needs questionnaire developed by our research group were used to investigate. Independent samples t-test or one-way ANOVA was used to compare the differences in the scores of different characteristics, and the factors with significant differences were selected for multivariate linear regression analysis to determine the final influencing factors. Results The total score of home hospice needs of the dying older adult was 115.70 ± 12, with the mean scores for each dimension in descending order being Information Needs (3.96 ± 0.61), Social Support Needs (3.96 ± 0.44), Spiritual Needs (3.92 ± 0.43), Physical Needs (3.60 ± 0.59), Psychological Needs (3.37 ± 0.65). Status of residence, duration of illness (year), the type of disease, and self-care ability were influential factors in the total score of home hospice needs. Discussion The need for hospice care for the terminally ill older adult is high, and healthcare professionals should implement services according to the influencing factors of need to meet their multidimensional needs and improve their quality of life.